2020
DOI: 10.1101/2020.06.15.152751
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Production and analysis of a mammalian septin hetero-octamer complex

Abstract: supported by NIH/NIGMS grants 5RO1 GM097664-9 and 1R35 GM136337. We thank Robert Fairman and Ronen Marmorstein for access to analytical ultracentrifugation instrumentation. We thank Dr. Patrick Loll for critical reading of the manuscript and the p97 vector. We thank Meagan Tomasso for a critical reading of the manuscript and the SEPT2/6/7 complex. We thank the College of Medicine and the Department of Pharmacology and Physiology access to the Olympus FV3000 laser scanning confocal microscope. AbstractThe septi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 89 publications
(111 reference statements)
0
10
0
Order By: Relevance
“…Biochemical isolation of native septins from budding yeast, Drosophila and mammalian cells and tissues revealed that septins exist as stable heteromeric complexes that can polymerize into filaments and higher-order filament assemblies (Field et al, 1996; Frazier et al, 1998; Hsu et al, 1998; Kim et al, 2011; Kinoshita et al, 2002; Sellin et al, 2011). The isolation of recombinant septin complexes helped establish that septin complexes are palindromes, with each septin in two copies and in a specific position within the complex, with each monomer interacting with its neighbors by alternating interfaces, named NC (from the N- and C-terminal domains) and G (from the GTP-binding domain) (Bertin et al, 2008; DeRose et al, 2020; Farkasovsky et al, 2005; Garcia et al, 2011; Huijbregts et al, 2009; Iv et al, 2021; John et al, 2007; Kinoshita et al, 2002; Kumagai et al, 2019; Mavrakis et al, 2014; Mendonca et al, 2019; Rosa et al, 2020; Sala et al, 2016; Sirajuddin et al, 2007; Soroor et al, 2021; Versele and Thorner, 2004). Human septins are classified in four homology groups, namely the SEPT2 group (SEPT1, 2, 4, and 5), SEPT6 group (SEPT6, 8, 10, 11, and 14), SEPT7 group (SEPT7), and SEPT3 group (SEPT3, 9, and 12) (Kinoshita, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical isolation of native septins from budding yeast, Drosophila and mammalian cells and tissues revealed that septins exist as stable heteromeric complexes that can polymerize into filaments and higher-order filament assemblies (Field et al, 1996; Frazier et al, 1998; Hsu et al, 1998; Kim et al, 2011; Kinoshita et al, 2002; Sellin et al, 2011). The isolation of recombinant septin complexes helped establish that septin complexes are palindromes, with each septin in two copies and in a specific position within the complex, with each monomer interacting with its neighbors by alternating interfaces, named NC (from the N- and C-terminal domains) and G (from the GTP-binding domain) (Bertin et al, 2008; DeRose et al, 2020; Farkasovsky et al, 2005; Garcia et al, 2011; Huijbregts et al, 2009; Iv et al, 2021; John et al, 2007; Kinoshita et al, 2002; Kumagai et al, 2019; Mavrakis et al, 2014; Mendonca et al, 2019; Rosa et al, 2020; Sala et al, 2016; Sirajuddin et al, 2007; Soroor et al, 2021; Versele and Thorner, 2004). Human septins are classified in four homology groups, namely the SEPT2 group (SEPT1, 2, 4, and 5), SEPT6 group (SEPT6, 8, 10, 11, and 14), SEPT7 group (SEPT7), and SEPT3 group (SEPT3, 9, and 12) (Kinoshita, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The most convincing evidence that septins form filaments in vivo , and that cell viability depends on their ability to assemble into filaments, comes from electron microscopy and functional data in budding yeast (Bertin et al, 2012; Byers and Goetsch, 1976; McMurray et al, 2011; Ong et al, 2014; Rodal et al, 2005). The conservation of septins and the ability of recombinant and cell-purified mammalian septin hexamers and octamers (hereafter referred to as protomers) to self-assemble into filaments in solution and on lipid membranes (DeRose et al, 2020; Iv et al, 2021; Leonardo et al, 2021; Soroor et al, 2021; Szuba et al, 2021) has led to the assumption that human septins also organize as filaments in cells, but formal evidence that this is the case is scarce. Immunogold electron microscopy in mammalian cells has shown gold-decorated septins in close apposition to cortical actin filaments and to the plasma membrane organizing in linear arrays (Hagiwara et al, 2011; Kinoshita et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies using recombinant mammalian septin complexes have combined septins from two or more species, most likely for pragmatic reasons. Mouse SEPT2 was combined with human SEPT6 and SEPT7 (Kinoshita et al, 2002;Mavrakis et al, 2014;Sirajuddin et al, 2007), or with human SEPT6, SEPT7 and SEPT3 (DeRose et al, 2020), and mouse SEPT2 was also combined with human SEPT6 and rat SEPT7 (Bai et al, 2013). There are currently no studies showing whether these specific species-related differences affect septin function.…”
Section: Introductionmentioning
confidence: 99%
“…26 However, recent studies have revised the order of mammalian septin complexes and revealed the position of SEPT2 at the ends of the octamer. [27][28][29] So the order suggested by Kuo et al probably should be inverted, and we might expect 2-6-7-12-12-7-6-2 or 4-6-7-12-12-7-6-4 positions in octamers. SEPT2 and SEPT4 occupy the same position in this complex.…”
mentioning
confidence: 85%
“…Kuo et al have revealed that SEPT2, 4, 6, 7, and 12 proteins are the annulus components forming 12‐7‐6‐2‐2‐6‐7‐12 or 12‐7‐6‐4‐4‐6‐7‐12 octamers 26 . However, recent studies have revised the order of mammalian septin complexes and revealed the position of SEPT2 at the ends of the octamer 27‐29 . So the order suggested by Kuo et al probably should be inverted, and we might expect 2‐6‐7‐12‐12‐7‐6‐2 or 4‐6‐7‐12‐12‐7‐6‐4 positions in octamers.…”
Section: Introductionmentioning
confidence: 96%